Ecotoxicological Effects on Apporectoda longa (Earthworm) and Telfairia occidsentalis (Pumpkin Plant) by Hair Dressing Salon Effluents from shops in Azu Owa, Ika Northeast Local Government Area, Delta State, Nigeria - L. U. Oshilonyah; I. M. Oyem; J. C. Igborgbor; E. I. Atuanya (Journal of Applied Sciences and Environmental Management)
The hairdressing salon industry produces waste containing various alkalis, relaxers, dyes, and chemicals, resulting in significant environmental concerns due to the uncontrollable nature of salon wastewater. Hence the objective of this paper was to evaluate the ecotoxicological effects on Apporectoda longa (Earthworm) and Telfairia occidentalis (pumpkin plant) by hair dressing salon effluents from shops Azu Owa community in Ika northeast local government area of Delta State, Nigeria using standard methods. Physicochemical analyses of soil samples showed pH levels ranging from 3.3 to 3.6 and clay content between 3% to 5%, both below WHO limits. The total solids of the effluent ranged from 3012 - 6443.8 mg/l, indicating high significance (p<0.05), while other parameters were not statistically significant. Heterotrophic bacteria count showed no significant differences (p>0.05), while soil fungal counts (4.67 + 1.70 -11.33 + 1.25 x 10^3 cfu/g) were significantly different (p<0.05) compared to the effluent. Acute toxicity assessments revealed no significant effects on earthworm length and weight across concentrations of 50 mg/ml to 200 mg/ml (p>0.05). Telfairia occidentalis exhibited significant differences in growth during weeks one and two (p<0.05), with no notable effects observed in week three. The results demonstrate a dose-dependent relationship between effluent concentration and earthworm mortality, with higher concentrations leading to increased lethality and observable behavioral alterations. These findings highlight the ecological risks associated with improper salon waste disposal. Earthworms, as bioindicators of soil health, underscore the need for effective waste management practices in the beauty industry. Further research is necessary to explore sub-lethal effects and long-term impacts on soil ecosystems from chronic exposure to these pollutants.